Information Technology for Travel Agency - E S Soegoto; A H Nugroho (Universitas Komputer Indonesia, 2021)
The purposes of this research are to describe, analyze, and determine the online marketing strategy of domestic travel agent at Bandung Tour Expert. In this case, the authors focused on SWOT analysis to find out the right marketing strategy for the tour packaging. In this research, the data was collected using the observation method, meanwhile the data analysis method used were descriptive qualitative and SWOT analysis. Internet users number are increasing, especially adults with high mobility. For them who often travel outside the city, internet is crucial because it connects them with the travel agent. Nowadays, the convenient use of Internet technology is used to market products and services offered by travel agents, so that it provides many benefits for business travel agents with minimum marketing costs. The results of this study were the use of internet and online marketing had impacts on the increasing profits of the travel agents. The conclusion of this research is Bandung Tour Expert as a company need to improve their variant of tour package to make tourist more interest to visit the company website.